Maternal Nutrition and Its Impact on Low Birth Weight in Newborns - Sana; Sajid, Irum; Khan, Sher Alam; Hussain, Shafqat; Masood Ur Rehman; Adnan, Mian Sohail (Indus Journal of Bioscience Research, 2025)
Maternal nutrition and its effects on birth weight especially with reference to dietary inadequacy, socio demographic status and health services. Using a mixed-methods approach, data from 300 postpartum women revealed significant nutritional gaps, including insufficient energy (mean intake: Energy (1800 kcal vs. recommended 2500 kcal), protein (45 g vs. 75 g), and micronutrients including iron, calcium, and vitamin D. These deficiencies were strongly associated with LBW, with multivariate regression showing significant odds ratios for energy (AOR: 2.privilege were significantly associated with higher energy intake (AOR: 5.0; 95% CI: 1.6–4.0) and higher protein intake (AOR: 3.1; 95% CI: 1.9–5.2). The study also realized that 33.3% of infants were categorized as LBW, which was similar to the current global statistics of low-income settings. The study affirmatively confirms maternal dietary interventions, use of supplementation, and the improvements in socio-economic wellbeing and its cruciality for decreasing the LBW prevalence. This research gives practical recommendations to both policy makers and health care practitioners who wish to enhance maternal and neonatal health.